The Salutogenic Basis for Personal Hardiness - Serdiuk, Liudmyla; Kuprieieva, Olga; Otenko, Svitlana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
The article analyzes the salutogenic approach in psychology, reveals the role of an individual’s salutogenic attitudes to help counteract stress impact. The relationship between the constructs of salutogenesis and an individual’s hardiness are analyzed. An individual’s salutogenic orientation is understood by us as his/her value attitude to his/her own psychological health; and health is considered not as an absent illness, but as a state in the continuum between mental disorder and psychological well-being. The integral indicator of a valuable attitude to health is a sense of coherence as a special structure of attitudes that includes three interrelated components: comprehensibility, manageability, meaningfulness.The study purpose is to determine empirically the salutogenic factors of an individual’s hardiness. The study used the following methods: C. Riff’s Psychological Well-Being Scale; A. Antonovsky’s sense of connectedness scale, S. Maddi’s Hardiness Test; Zimbardo Time Perspective Inventory; Ways of Coping questionnaire by S. Folkman and R.S. Lazarus. The study sample consisted of 183 people, 48 men and 135 women; average age was 37.7 ± 11.1 years.The correlations among the components of salutogenetic orientation, hardiness, coping strategies and time perspective were determined empirically. The resources of an individual’s general resistance, which alleviate stress impact and contribute to the individual’s optimal functioning, are related to understanding and assessment of a situation by the individual, existing acknowledged life goals, the ability to influence life events, one's own capabilities understood by the individual and existing positive relationships with others.
Keywords: salutogenesis; hardiness; personal resources; coping strategies; time perspective